The party and state USSR leaders about concessions (1920th) - Julia Yakovenko (Cхід, 2013)
The article considers the estimate of tasks, prospects and results of foreign capitals involving, on concession basis in the soviet economy in the years of new economic policy, by party-and-state figures of theUSSR. Bolsheviks studied the existent concession experience long ago, tried to use it efficiently in the conditions of new economic policy. Examining of works and speeches of the well-known bolsheviks allowed to define defenders and opponents of concession policy. V. Lenin, L. Krasin, O. Rykov supported wide use of concessions. They considered that this form of collaboration with foreign businessmen can have a large socio-economic and political meaning, however they always understood and indicated in the speeches the necessity of carefulness, attentiveness in negotiations with foreign businessmen, in entering into agreements. A. Ioffe, G. Chicherin suggested to use the concession propositions in diplomacy. F. Dzerzhinskiy more carefully spoke about the benefit from concessions and stood almost neutral position. L. Trockiy, M. Bukharin with the lapse of time became the defenders of idea ofUSSReconomy independent revival without a foreign help. Changes in their looks were related to small specific importance of concession enterprises in the national economy of theUSSRand successes of state industry. The opponent of concessions in the soviet country was Y. Stalin. He thought that concession development can turnRussiainto a colony. Negative attitude towards concession business in high party-and-state leaders' surroundings prevailed, especially in the second half of 1920th; this caused the refusal of concessions and new economic policy in the whole. Herewith all the opponents of concession policy followed not economic expediency, but class interests. With the lapse of time in connection with the gradual overcoming of crisis, state industry successes, the idea of economy development of theUSSRwithout the foreign help became dominant.